Mobile Health Quality among National Health Insurance Participants in South Sumatra - Idris, Haerawati; Misnaniarti, Misnaniarti; Safriantini, Dian (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
The development of information technology and telecommunications has penetrated into various sectors including health.Ã‚Â WithÃ‚Â MobileÃ‚Â JKN, communityÃ‚Â administrative activitiesÃ‚Â in managingÃ‚Â JKNÃ‚Â are easier. The study aims to analyze theÃ‚Â perceptionÃ‚Â of mobile healthÃ‚Â among participants JKNÃ‚Â in South Sumatra Province.Ã‚Â ThisÃ‚Â researchÃ‚Â isÃ‚Â a quantitative studyÃ‚Â with aÃ‚Â cross-sectionalÃ‚Â design.Ã‚Â The research sample was JKN participants stay in South SumatraÃ‚Â aged> 18 years whoÃ‚Â use theÃ‚Â MobileÃ‚Â JKNÃ‚Â appÃ‚Â amountÃ‚Â 400Ã‚Â participants.Ã‚Â The sampling technique used purposive sampling.Ã‚Â Data collectionÃ‚Â usingÃ‚Â onlineÃ‚Â questionnairesÃ‚Â and distributed through social media.Ã‚Â Results of the studyÃ‚Â showed that the perception of theÃ‚Â quality system has optimal results (50,50%).Ã‚Â The problem encountered was in theÃ‚Â network stabilityÃ‚Â indicatorÃ‚Â from JKN mobile application users.Ã‚Â On the quality of information has optimal results(67.50%).Problems encountered are in the indicator ofÃ‚Â limitedÃ‚Â serviceÃ‚Â information,Ã‚Â displayÃ‚Â updates.Ã‚Â Then, the quality of service has optimal results (63,50%).Ã‚Â The problem encountered was in theÃ‚Â service integrationÃ‚Â indicatorÃ‚Â from the JKN mobile application.Ã‚Â Quality of theÃ‚Â JKNÃ‚Â MobileÃ‚Â applicationÃ‚Â seen from the System Quality, Information Quality and Service Quality has optimal results.Ã‚Â BPJS Health suggested to increase network stability, improve service information,Ã‚Â displayÃ‚Â updatesÃ‚Â and information in theÃ‚Â JKNÃ‚Â MobileÃ‚Â application, conduct application socialization,Ã‚Â andÃ‚Â develop service integration.